Equilibrium morphology and scour evolution at blunt nosed chevrons. (2nd December 2021) - Roy, Deep; Pagliara, Simone
Abstract: Blunt nosed chevrons are low‐head river restoration structures commonly used in large rivers to enhance the navigation and aquatic habitat. These structures usually create scour regions in their vicinity, which provides habitat for various aquatic organisms. Furthermore, the scour pools represent suitable locations for fish nursery. In some cases, the noses of islands are protected by constructing chevrons which reduce the intensity of erosive action. Only a few studies deal with the analysis of the scour phenomena due to chevrons. Therefore, this paper aims at investigating the scour evolution and characteristics at equilibrium due to chevrons inserted in both straight and curved channels. The most influential parameters governing the scour mechanisms (e.g., densimetric Froude number) were identified via dimensional analysis. Experimental evidence allowed us to distinguish and classify different scour morphology types for chevrons in curved channels: Types A b, B b and C b were identified, corresponding to Types A, B and C in straight channels. Moreover, useful empirical relationships are provided to estimate the maximum scour hole depth and length, and the dune height with sufficient accuracy ( R 2 ranging from 0.63 to 0.86). Finally, the equations are validated with the data from previous studies, showing a good predicting capacity.